THE ROLE AND IMPORTANCE OF PROBLEMS IN THE FORMATION OF STUDENTS' MATHEMATICAL KNOWLEDGE - Salikhova Olga Valerievna (American Journals Publishing, 2022)
In this article, opinions were expressed about the role and importance of problems in the formation of students' mathematical knowledge.
Keywords: technology, geometry, technique, problem, logical thinking